Multilocus phylogeny of the avian family Alaudidae (larks) reveals complex morphological evolution, non-monophyletic genera and hidden species diversity - Alström, Per; Barnes, Keith N.; Barker, F. Keith; Olsson, Urban; Bloomer, Paulette; Khan, Aleem Ahmed; Qureshi, Masood Ahmed; Guillaumet, Alban; Crochet, Pierre-André; Ryan, Peter G. (2013)
The Alaudidae (larks) is a large family of songbirds in the superfamily Sylvioidea. Larks are cosmopolitan, although species-level diversity is by far largest in Africa, followed by Eurasia, whereas Australasia and the New World have only one species each. The present study is the first comprehensive phylogeny of the Alaudidae. It includes 83.5% of all species and representatives from all recognised genera, and was based on two mitochondrial and three nuclear loci (in total 6.4 kbp, although not all loci were available for all species). In addition, a larger sample, comprising several subspecies of some polytypic species was analysed for one of the mitochondrial loci. There was generally good agreement in trees inferred from different loci, although some strongly supported incongruences were noted. The tree based on the concatenated multilocus data was overall well resolved and well supported by the data. We stress the importance of performing single gene as well as combined data analyses, as the latter may obscure significant incongruence behind strong nodal support values. The multilocus tree revealed many unpredicted relationships, including some non-monophyletic genera (Calandrella, Mirafra, Melanocorypha, Spizocorys). The tree based on the extended mitochondrial data set revealed several unexpected deep divergences between taxa presently treated as conspecific (e.g. within Ammomanes cinctura, Ammomanes deserti, Calandrella brachydactyla, Eremophila alpestris), as well as some shallow splits between currently recognised species (e.g. Certhilauda brevirostris-C semitorquata-C curvirostris; Calendulauda barlowi-C. erythrochlamys; Mirafra cantillans-M. javanica). Based on our results, we propose a revised generic classification, and comment on some species limits. We also comment on the extraordinary morphological adaptability in larks, which has resulted in numerous examples of parallel evolution (e.g. in Melanocorypha mongolica and Alauda leucoptera [both usually placed in Melanocorypha]; Ammomanopsis grayi ...